Rescue of cardiomyopathy through U7snRNA‐mediated exon skipping in Mybpc3‐targeted knock‐in mice. Issue 7 (29th May 2013) - Gedicke‐Hornung, Christina; Behrens‐Gawlik, Verena; Reischmann, Silke; Geertz, Birgit; Stimpel, Doreen; Weinberger, Florian; Schlossarek, Saskia; Précigout, Guillaume; Braren, Ingke; Eschenhagen, Thomas; Mearini, Giulia; Lorain, Stéphanie; et al.
Abstract: Exon skipping mediated by antisense oligoribonucleotides (AON) is a promising therapeutic approach for genetic disorders, but has not yet been evaluated for cardiac diseases. We investigated the feasibility and efficacy of viral‐mediated AON transfer in a Mybpc3 ‐targeted knock‐in (KI) mouse model of hypertrophic cardiomyopathy (HCM). KI mice carry a homozygous G>A transition in exon 6, which results in three different aberrant mRNAs. We identified an alternative variant (Var‐4) deleted of exons 5–6 in wild‐type and KI mice. To enhance its expression and suppress aberrant mRNAs we designed AON‐5 and AON‐6 that mask splicing enhancer motifs in exons 5 and 6. AONs were inserted into modified U7 small nuclear RNA and packaged in adeno‐associated virus (AAV‐U7‐AON‐5+6). Transduction of cardiac myocytes or systemic administration of AAV‐U7‐AON‐5+6 increased Var‐4 mRNA/protein levels and reduced aberrant mRNAs. Injection of newborn KI mice abolished cardiac dysfunction and prevented left ventricular hypertrophy. Although the therapeutic effect was transient and therefore requires optimization to be maintained over an extended period, this proof‐of‐concept study paves the way towards a causal therapy of HCM. Abstract : Exon skipping is a promising therapy for selected genetic diseases. Here, the authors show as a proof‐of‐principle that MYBPC3 mutation‐induced cardiomyopathy can be rescued by AAV‐U7‐antisense oligoribonucleotides in the heart of neonatal mice.